Posttraumatic Growth, Positive Psychology, Perceived Spousal Support, and Psychological Complications in Head and Neck Cancer: Evaluating Their Association in a Longitudinal Study - Nik Jaafar, Nik Ruzyanei; Abd Hamid, Norhaliza; Hamdan, Nur Amirah; Rajandram, Rama Krsna; Mahadevan, Raynuha; Mohamad Yunus, Mohd Razif; Zakaria, Hazli; Mohd Shariff, Noorsuzana; Hami, Rohayu; Isa, Salbiah; Shari, Nurul Izzah; Leong Bin Abdullah, Mohammad Farris Iman (Frontiers in Psychology, 2022)
Despite head and neck cancer (HNC) association with various negative impacts, collective evidence is accumulating regarding the positive impacts of positive psychology on cancer survivors. However, data on how positive psychology is related to the psychological complications of HNC across time are lacking. This longitudinal study examined the trends of positive psychology (e.g., posttraumatic growth [PTG], hope, and optimism), perceived spousal support, and psychological complications (e.g., depression, anxiety, and posttraumatic stress symptoms) and determined the association between them, psychological complications, and PTG across two timelines among a cohort of HNC patients. A total of 175 HNC respondents exhibited an increasing trend of positive psychology and perceived spousal support while reporting a decreasing trend of psychological complications between baseline and follow-up assessments. A greater degree of hope and perceived spousal support contributed to a higher degree of PTG across time. Conversely, a higher severity of anxiety symptoms was associated with a lower degree of PTG over time. Female gender had a moderating effect on the association between severity of anxiety symptoms and PTG, but did not moderate the association between hope, perceived spousal support and PTG. This study indicates the pivotal role of incorporating psychosocial interventions into the treatment regimen to enhance the degree of hope and perceived spousal support and reduce the severity of anxiety symptoms, which, in turn, will facilitate the development of PTG in HNC patients.